Accessory diaphragm associated with non-immune hydrops fetalis. (4th July 2014) - Priyadarshi, Archana; Sugo, Ella; Challis, Daniel; Bolisetty, Srinivas
Abstract : An accessory diaphragm, also known as diaphragmatic duplication, is a congenital anomaly in which there is a fibromuscular membrane on top of the normally formed diaphragm dividing the hemithorax into two compartments trapping part of the pulmonary parenchyma. It is a very rare anomaly with less than 40 cases reported in the literature, of which only five were diagnosed in the newborn period, with no reports on any clinical clues for the antenatal diagnosis of this condition. We describe a case of congenital accessory diaphragm presenting in the antenatal period as hydrops fetalis. We also describe the radiological features of this rare anomaly on the antenatal fetal ultrasound.